Besedotvorna teorija Ju. D. Apresjana na poti k tipologiziranju slovarske večpomenskosti - Snoj, Jerica (Slavistična revija, 2004)
In some metonymic meaning one can establish the congruity of internal lexical inter-semantic relations with the realitons between the elements of the proposition. The idea for this kind of typology of metonymic polysemy of nouns regardless of the presence of derivational menaing derives from the theory of Y. D. Apresyan, who treats the polysemy and semantic derivation within broadly defined word derivation.
Keywords: Apresjan, Jurij Derenikovič; besedotvorje; leksikografija; lexicography; sintaksa; večpomenskost; word formation